Long-term and seasonal variability of snow blanket thickness at the Galindez glacier - Belokrinitskaya, L. M.; Grischenko, V. F.; Ivchenko, V. N.; Klock, S. V.; Kruchenitsky, G. M. (Ukrainian Antarctic Journal, 2006)
Periodical and irregular components of variations in snow blanket thickness at the Galindez Island, the Argentine Islands archipelago, were statistically analyzed. Multiplicative model of temporal series of this thickness was created, amplitudes and phases of spectral components were determined, statistically significant positive trend was revealed, its value was 5 percents per year. An estimation of characteristic time for variations in snow blanket thickness was made upon this base and this thickness was forecasted for next two years.